Problems and prospects of legal regulation of land use in the North Kazakhstan region: legal and institutional analysis - Kaskeeva, A.Z. (Bulletin of the Karaganda University “Law Series”, 2025)
The article is devoted to a comprehensive legal and institutional analysis of land use in the North Kazakhstan Region (NKR) of the Republic of Kazakhstan, one of the country’s key agricultural regions. It examines both fundamental and applied aspects of the regulatory framework governing land relations, including the provi sions of the Constitution, the Land Code, by-laws, as well as national and regional programs such as the Agro-Industrial Complex Development Concept, the “Digital Kazakhstan” program, and targeted projects for preserving soil fertility. Special attention is given to current challenges in the practical implementation of land policy: inefficient and unbalanced use of agricultural land, disparities in the distribution of land re sources between large Agricultural Holdings and small farms, insufficient digitalization of the cadastral sys tem, weak integration of information technologies, and limited control over compliance with environmental standards and soil protection regulations. Based on official statistics, legal acts, and expert assessments, the author concludes that comprehensive modernization of land use regulation, enhanced monitoring, innovative agricultural technologies, and legal education programs for rural communities are necessary to ensure produc tive, sustainable, and equitable land use in the NKR.